PENGARUH CASH HOLDING, PROFITABILITAS, DAN NILAI PERUSAHAAN TERHADAP INCOME SMOOTHING (Studi Empiris Pada Perusahaan yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2011) - Yashinta Pradyamitha Cendy; Fuad Fuad (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of variable cash holding, positive changes in cash holding, profitability, and firm value to income smoothing. Based on firm size measured by using natural logarithm of total assets. This research refers to research conducted Talebnia and Darvish ( 2012), the effect of cash holdings on income smoothing in companies listed on the Tehran Stock Exchange. The sampling method used in this research is purposive sampling, that is  based on several criteria.The sample of this study are 99 sample of manufacturing and service companies (except financial service companies) listed in Indonesia Stock Exchange (IDX) 2009-2011. The analysis method of this research using multiple regression using SPSS 16. This study uses multiple regression analysis because there is a control variable. This research also use difference of regression coefficient test to examine differences between the two regression coefficients of the independent variable of manufacture and service companies to income smoothing.Based on the results of research conducted indicates that the variable holding cash, profitability, and firm size as control variables significantly influence income smoothing. Different test results show that the profitability of the regression coefficient for income smoothing has the effect of differences between manufacturing and service companies, as profits in manufacturing companies is more volatile, while profits in service firms is relatively stable, so that the tendency to make greater income smoothing in manufacturing companies .